Pre-Cooling and sports performance: A meta-analytical review - Wegmann, M.; Faude, O.; Poppendieck, W.; Hecksteden, A.; Fröhlich, M.; Meyer, T. (Sports Medicine, 2012)
Pre-cooling is used by many athletes for the purpose of reducing body temperature prior to exercise and, consequently, decreasing heat stress and improving performance. Although there are a considerable number of studies showing beneficial effects of pre-cooling, definite conclusions on the effectiveness of pre-cooling on performance cannot yet be drawn. Moreover, detailed analyses of the specific conditions under which pre-cooling may be most promising are, so far, missing. Therefore, we conducted a literature search and located 27 peer-reviewed randomized controlled trials, which addressed the effects of pre-cooling on performance. These studies were analysed with regard to performance effects and several test circumstances (environmental temperature, test protocol, cooling method, aerobic capacity of the subjects).